2002
DOI: 10.1007/s00442-002-0959-8
|View full text |Cite
|
Sign up to set email alerts
|

Microsite characteristics of Muhlenbergia richardsonis (Trin.) Rydb., an alpine C4 grass from the White Mountains, California

Abstract: C plants are uncommon in cold environments and do not generally occur in the alpine tundra. In the White Mountains of California, however, the C grass Muhlenbergia richardsonis is common in the alpine zone at 3,300-3,800 m, with the highest population observed at 3,960 m (13,000 feet) above sea level. This is the highest reported C species in North America and is near the world altitude limit for C plants (4,000-4,500 m). Above 3,800 m, M. richardsonis is largely restricted to southern slope aspects, with grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Most of these studies have focused on low temperatures during the growing season, but our results suggest that winter temperatures may be equally important in limiting C 4 grasses. Some C 4 species can tolerate cold temperatures when dormant (Schwarz and Reaney, 1989) and during the growing season (Sage and Sage, 2002), but a late hard freeze after germination may limit establishment by impacting the chilling-susceptible seedlings in many species. For example, Zea mays exhibits loss of photosynthetic capacity due to photoinhibition during periods of high light intensity and low temperatures.…”
Section: Late Pleistocene Climatementioning
confidence: 99%
“…Most of these studies have focused on low temperatures during the growing season, but our results suggest that winter temperatures may be equally important in limiting C 4 grasses. Some C 4 species can tolerate cold temperatures when dormant (Schwarz and Reaney, 1989) and during the growing season (Sage and Sage, 2002), but a late hard freeze after germination may limit establishment by impacting the chilling-susceptible seedlings in many species. For example, Zea mays exhibits loss of photosynthetic capacity due to photoinhibition during periods of high light intensity and low temperatures.…”
Section: Late Pleistocene Climatementioning
confidence: 99%
“…Schwarz and Redmann (1987) and Sage and Sage (2002) suggest further studies for a better understanding of resistance mechanisms of grass species distributed in low temperature environments. Pearcy (2001) and Márquez (2002) also highlight the importance of understanding freezing in plants as a distributional pattern constraint.…”
Section: Introductionmentioning
confidence: 99%
“…Some C 4 species do exploit high latitude or high elevation sites, however, indicating that C 4 photosynthesis is not fundamentally excluded from such areas (Long et al 1975;Schwarz and Redmann 1988;Sage and Sage 2002). One possible explanation for their occurrence in colder locations is that their greater water and nitrogen use efficiency (WUE and NUE, respectively) relative to cooccurring C 3 species may offset the deleterious effects of low temperatures.…”
mentioning
confidence: 92%
“…Schwarz and Redmann (1988) suggested that boreal C 4 species are limited to microsites warmed by light or geothermal activity, perhaps enabling them to avoid the problems associated with low temperatures. In the alpine zone of the White Mountains of California, Muhlenbergia richardsonis is restricted to the warmest slope-aspects, and takes advantage of the ground boundary layer to attain leaf temperatures that are favourable to C 4 photosynthesis (Sage and Sage 2002). In cool climates, specific microsite characteristics may thus enable the C 4 pathway to persist, despite the fundamental limitation imposed by their low quantum yield and low Rubisco content.…”
mentioning
confidence: 99%